Transcriptomic analysis of differential gene expression during chick periocular neural crest differentiation into corneal cells. Issue 7 (2nd May 2019) - Bi, Lian; Lwigale, Peter
Abstract: Background: Multipotent neural crest cells (NCC) contribute to the corneal endothelium and keratocytes during ocular development, but the molecular mechanisms that underlie this process remain poorly understood. We performed RNA‐Seq analysis on periocular neural crest (pNC), corneal endothelium, and keratocytes and validated expression of candidate genes by in situ hybridization. Results: RNA‐Seq profiling revealed enrichment of genes between pNC and neural crest‐derived corneal cells, which correspond to pathways involved in focal adhesion, ECM‐receptor interaction, cell adhesion, melanogenesis, and MAPK signaling. Comparisons of candidate NCC genes to ocular gene expression revealed that majority of the NCC genes are expressed in the pNC, but they are either differentially expressed or maintained during corneal development. Several genes involved in retinoic acid, transforming growth factor‐β, and Wnt signaling pathways and their modulators are also differentially expressed. We identified differentially expressed transcription factors as potential downstream candidates that may instruct expression of genes involved in establishing corneal endothelium and keratocyte identities. Conclusion: Combined, our data reveal novel changes in gene expression profiles as pNC differentiate into highly specialized corneal endothelial cells and keratocytes. These data serve as platform for further analyses of the molecular networks involved in NCC differentiation into corneal cells and provide insights into genes involved in corneal dysgenesis and adult diseases. Key Findings: RNA‐Seq profiling revealed enrichment of genes between periocular neural crest corneal endothelium, and keratocytes. The top KEGG pathways of the differentially express genes include focal adhesion, ECM‐receptor interaction, cell adhesion, melanogenesis, and MAPK signaling. Candidate neural crest genes are expressed in the periocular neural crest, but they are either differentially expressed or maintained during cornea development. Modulators of major signaling pathways associated with ocular development (retinoic acid, TGFß, and Wnt), transcription factors, and differentiation genes were differentially expressed.